Characterization of a supersonic molecular beam for charged particle beam profile monitor. (February 2023) - Zhang, H.D.; Salehilashkajani, A.; Sedlacek, O.; Welsch, C.P.
Abstract: In the present work, we report an experimental method to measure the density and distribution of a supersonic molecular beam used for charged particle beam profile monitoring. The density of the molecular beam used in this monitor was in the range of 1 0 14 – 1 0 17 molecules/m 3 . The vacuum performance of such a system using beam-induced fluorescence mode was discussed. The successful measurement of the molecular beam parameters paves the way for future applications in beam profile monitors for machines such as the LHC and proton therapy accelerators. Highlights: Development of non-invasive charged particle beam profile monitor. Vacuum system to generate a supersonic gas curtain. Methods for measuring the density distribution of a molecular beam. Characterization of a molecular beam for accelerator diagnostics.